Veterans, Firearms, and Suicide: Safe Storage Prevention Policy and the PREVENTS Roadmap - Lemle, Russell B. (Fed Pract, 2020)
BACKGROUND: US veterans die by suicide at a higher rate than that of the civilian population and are more likely to use a firearm as their method. Systemic efforts to address the use of firearms in suicide had been largely evaded. In June 2020, the White House published the Roadmap to Empower Veterans and End the National Tragedy of Suicide (PREVENTS) task force report, which verified the link between, and the need to address, at-risk veterans and their access to firearms. This paper reviews the literature on the intersection of veterans, firearms, and suicide, then explores existing VA prevention initiatives aimed at reducing at-risk veterans’ access to lethal means and offers policy recommendations to expand efforts in the context of the PREVENTS Roadmap. OBSERVATIONS: The PREVENTS report recommends widespread distribution of safety education materials that encourage at-risk individuals to temporarily transfer or store their guns safely and the expansion of free or affordable options for storing weapons. Recommended policy actions to accomplish this goal include delaying access to firearms for at-risk veterans, facilitating temporary storage out of the home, improving in-home safe storage options, requiring that health care providers who care for high-risk veterans are trained in lethal means safety counseling, and creating campaigns to shift cultural norms for firearms’ storage during crises. CONCLUSIONS: Suicide prevention requires a multimodal approach, and attention to firearms access must become a more salient component. The high rate of veteran suicides involving firearms requires far-reaching interventions at societal, institutional, community, family, and individual levels.